Kriminalisasi Kemiskinan dalam Perspektif Sosiologi Hukum terhadap Kebijakan Penertiban Masyarakat Marginal - Fitri Jihad Aminah; Siti Kuraesin; Agus Nandar Syaripudin; Rizal Mutaqin; Beni Ahmad Saebani (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the policy of regulating marginalized poor communities in the context of legal sociology, as well as the impact of the policy of regulating marginalized communities socially and legally. This research uses a normative method with a legal sociology approach to analyze policing policies against marginalized communities as a form of criminalization of poverty. Research focuses on written and unwritten legal norms related to poverty and human rights. The main data source includes statutory regulations, while secondary data consists of literature and expert opinions. Data collection techniques use library research, with qualitative analysis based on legal sociology theory. The results of this research show that marginal poor communities in Indonesia live in limited socio-economic conditions, often face discrimination, and are marginalized by policies that do not support them. Social inequality between rural and urban areas is still significant. Repressive policing policies, such as forced evictions and criminalization of informal activities, worsen their situation. This research emphasizes the need for social justice-based policies that empower marginalized communities, as well as legal reform to create a more inclusive and fair system. The active involvement of marginalized groups in policy making is very important to break the cycle of poverty and improve their welfare